The Role of Surgical Closure Position in Total Knee Arthroplasty: Flexion versus Extension—A Randomized Prospective Study - Pepe, Murad; Calisal, Emre; Kocadal, Onur; Bicer, Eren; Taskin, Suhan; Aktekin, Cem Nuri (The Journal of Knee Surgery, 2019)
We aimed to investigate the effect of the knee position during the surgical closure on isokinetic muscle strength, clinical score, and range of motion in total knee arthroplasty. Seventy-five eligible patients were enrolled in the study and randomly divided into two groups; wound closure was performed with the knee flexed at 90° in group 1 and knee extended in group 2. All the surgeries were performed by the same surgeon and by the same prosthesis type. All the patients received the same rehabilitation program postoperatively. The primary outcomes were the knee flexion degrees and the American Knee Society Score values at preoperative and postoperative 6 weeks, 3, and 6 months. The secondary outcome was the isokinetic muscle strength measurements of both knees before the surgery and after 6 months. There were no significant differences in the American Knee Society Scores and knee flexion degrees between the flexion and extension groups. However, a significant decrease was found in the extensor muscle strength in the extension group after 6 months of the surgery. The findings of our study are that the closing of the knee in flexion or extension does not affect the postoperative knee flexion degrees and scores in total knee arthroplasty. However, quadriceps strength recovers early if the knee closure is performed in flexion position.
Keywords: wound closure; total knee arthroplasty; flexion; extension; isokinetic muscle strength